THE STRATEGY USING YOUTUBE AS DA’WAH MEDIA TODAY - Muzayyanah Yuliasih (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2022)
Background, Da’wah activities at this time can not only be done conventionally, but in this digital era preaching can be done through various media, not only through print and electronic media, but preaching can now be done through social media. One of the social media that can be used for preaching is YouTube social media, currently YouTube occupies the top position as the most popular video sharing. The study of digital da’wah on YouTube is still centered on preachers who already have big names, and also da’wah media that are already large in number of subscribers. In this study, the strategy for using YouTube as a medium of da’wah today will be studied. Method, This research is a qualitative method. The selection of this method is intended to find out how the data from the findings can be found, collected, processed, and analyzed. Discussion, Building a medium for delivering da’wah using Youtube is not as easy as conventionally delivering material. This is because, must pay attention to the various language and ethical rules in it. Thus, many adjustments are needed in providing religious information to the public. The editing process carried out also requires that it be done more carefully so that the desired content is really well received without any misunderstanding of information. So with the video method, the message of da’wah can be reached easily, and the people who watch it also understand the essence of the da’wah. This method has the most important position as a determinant of the success of preaching in this modern era.